IMPROVING TODDLER NUTRITION WITH CHILD MASSAGE AND MORINGA LEAVES CALLED TANJIDOR - Arlym, Lisa Trina; Rocady, Nila Waty; Rahmida, Rosi; Yuliani, Diah; Mardiana, Eka; Nurhasanah, Nurhasanah; Nurmaidah, Nurmaidah; Ferdiyanti, Rika; Salida, Siti Nurul (Yayasan Education and Social Center, 2025)
Stunting is a condition of growth failure in children under five due to chronic malnutrition, especially in the first 1,000 days of life, which is from the fetus in the womb until the child is two years old. Children who are stunted have a height below the age standard and are at risk of experiencing obstacles to cognitive, motor, and academic achievement in the future. Based on data from various health surveys, the prevalence of stunting in Indonesia is still at an alarming level, although it has shown a decline in recent years. The causes of stunting are complex and multidimensional, including lack of nutritional intake, unbalanced diets, poor sanitation, recurrent infections, and low levels of education and knowledge of mothers about child health and nutrition. The problem of stunting must be addressed seriously through a cross-sectoral approach involving the government, community, health workers, and families. Efforts to prevent and manage stunting should focus on specific and sensitive nutrition interventions, enhancing the quality of maternal and child health services, improving environmental sanitation, and promoting sustainable nutrition education. This community service activity aims to implement community midwifery care, which involves identifying problems, determining problem priorities, developing follow-up plans, implementing planned interventions, and evaluating the activities that have been This community service begins with FGDs to collect information on maternal and child problems. Priority problems are then selected based on the scale, and efforts are made to address stunting issues through education, demonstrations of preparing nutritious food using moringa leaves, and training parents and posyandu cadres in massaging children to stimulate weight growth. Intervention activities, including infant massage and supplementary feeding (PMT), were conducted over 4 weeks for 30 infants aged 6-12 months with growth disorders (BB/U < U <-2 SD). The monitoring results showed positive changes in both physical development and psychological responses of the infants. Following the implementation of the intervention, a notable change in body weight was observed, with an average weight gain of 400 grams over 4 weeks. Appetite Improvement: Based on the infant's mother's report, 76.7% of infants showed an increase in appetite after receiving a combination of infant massage and PMT. Motor and Psychological Development; Observations showed that infants who were regularly massaged showed improvement in fine and gross motor activities, such as rolling over, sitting up, and crawling. Parents also reported that infants seemed more relaxed, slept better, and cried less. Maternal Satisfaction and Acceptance Level: 90% of mothers were satisfied with the infant massage activities and stated that they would continue this practice at home. Additionally, 85% of mothers reported that the PMT provided was readily accepted by toddlers and practical to prepare at home. Community service, in the form of baby massage training for parents with toddlers and demonstrations of the production of moringa leaf-based personal care products (PMP), has a positive impact. Cadres and mothers are capable of comprehending the material and posing inquiries with enthusiasm. Understanding how to do child massage, mothers of toddlers also said they were happy because, later, they could easily practice cooking a Moringa Leaf Egg Omelet, which tasted good and had high nutritional value for children